AB0455 Good Response on Rituximab Treatment for Patients with Rheumatoid Arthritis Persists for Up to 4 Years. (9th June 2015) - Visman, I.M.; Agca, R.; Voskuijl, A.; Lems, W.; Nurmohamed, M.
Abstract : Background: With the advent of biological therapy a range of new drugs have come available for patients with rheumatoid arthritis (RA). Rituximab (RTX) is a lesser known, but effective treatment option for patients with RA. Obviously, data on long-term efficacy and safety in daily clinical practice is important as results obtained in short-term clinical registration trials might differ from those observed in long-term daily clinical practice. Objectives: To ascertain the efficacy of long- term RTX treatment for RA Methods: From February 2009 to February 2014, 97 consecutive patients were included in the rituximab for RA cohort at the Jan van Breemen research centre in Amsterdam, the Netherlands. Results: The mean age was 58 years (SD:13), and 74 (76%) were female. At baseline, the median disease duration was 12 (5-18) years, and 75 (79%) were Rheumatoid factor positive. At baseline, 38 (41%) used methotrexate, 46 (49%) used prednisolone, and 18 (19%) a DMARD other than MTX. On average patients had used 3.4 (SD:1.6) DMARDs, 1.5 (1.1) biologicals. At 72, most (77%) patients had used at least one biological prior to start of rituximab. A total of 66 (68%) patients are currently on drug, and 31 (32%) patients have dropped out. The median follow-up duration was 1.1 (IQR:0.6-1.9) years for patients currently still on rituximab treatment, and 0.6 (0.1-1.1) years for drop-outs. The maximum follow-up duration was 3.8 years. The mean DAS-28 dropped significantly from 5.2 (SD: 1.4) at baseline to 4.3 (1.4) at 12 weeks. This improvement was sustained, and steadily improved further over the whole 3 years (see figure ). The patient reported outcome of the health assessment questionnaire (HAQ) also showed a good initial response, however rose to baseline levels after 1.5 years before dropping again and much lower (see figure ). Conclusions: The initial good response on rituximab persists for at least 3 years of follow-up, with the decrease in DAS28 continuing for the entire 3 years. Over time, a satisfactory response both in HAQ and DAS28 was sustained. Disclosure of Interest: None declared